Pathogenesis and therapy of anemia in patients with inflammatory bowel diseases - O. V. Rybina; V. T. Sakhin; A. V. Gubkin; O. A. Rukavitsyn (Онкогематология)
Background. Anemia represents one of the most frequent complications in inflammatory bowel disease and severely impairs the quality of life of affected patients. The etiology of anemia in inflammatory bowel disease patients can be multifactorial, often involving a combination of iron deficiency anemia and anemia of chronic disease. The choice of therapy, focused on the leading cause of anemia, allows for individualized therapy, minimizing the risk of side effects and the cost of therapy.Aim. A comparative analysis of blood parameters before and after treatment was performed.Materials and methods. For 5 years, 47 patients (15 women, 32 men) with inflammatory bowel disease with a median age of 48 years (from 28 to 65 years) were studied. Two groups were formed: patients with iron deficiency anemia and patients with anemia of chronic disease. Patients with combination of iron deficiency anemia and anemia of chronic disease D (n = 21) were not included. A division was also made according to the type of treatment performed.Results. In the iron deficiency anemia group, a statistically significant increase in hemoglobin level was revealed as a result of the use of intravenous iron. During therapy with oral iron and B vitamin therapy, as well as therapy aimed only at correcting gastrointestinal tract pathology, no reliable dynamics of the studied parameters was observed. In the anemia of chronic disease group, there were no significant changes in red blood cell parameters with any of the treatment options (p >0.05).Conclusion. The effectiveness of various therapeutic approaches to correct anemia is controversial. Further follow-up and an increase in the sample size are needed, which will help individualize therapy and improve the patients’ quality of life.